4(3(2x-1)+7)-4=3(3(2x-1)+6
4(6x-3+7)-4=3(6x-3+6)
4(6x+4)-4=3(6x+3)
24x+16-4=18x+9
24x+12=18x+9
24x-18x=9-12
6x=-3
x=-1/2
или же х=-0.5
Ответ:
4(3(2x-1)+7)-4=3(3(2x-1)+6)
24x-18=9-12
x1=0,5 ;
Вроде так
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
4(3(2x-1)+7)-4=3(3(2x-1)+6
4(6x-3+7)-4=3(6x-3+6)
4(6x+4)-4=3(6x+3)
24x+16-4=18x+9
24x+12=18x+9
24x-18x=9-12
6x=-3
x=-1/2
или же х=-0.5
Ответ:
4(3(2x-1)+7)-4=3(3(2x-1)+6)
4(6x-3+7)-4=3(6x-3+6)
4(6x+4)-4=3(6x+3)
24x+16-4=18x+9
24x+12=18x+9
24x-18=9-12
6x=-3
x1=0,5 ;
Вроде так